Normative data of the teacher self-efficacy scale in Chilean elementary school teachers - Salvo-Garrido, Sonia; Polanco-Levicán, Karina; Dominguez-Lara, Sergio; Gálvez-Nieto, José Luis (Frontiers in Education, 2025)
Self-efficacy is crucial to teaching performance; it enables teachers to establish positive relation-ships with students, cope with work challenges, and promote academic success. Assessing perceived self-efficacy is vital because it directly impacts daily pedagogical practices. This study sought to establish normative data for interpreting the Teachers’ Sense of Efficacy Scale (TSES) scores among Chilean elementary school teachers. The sample included 1,426 first- to eighth-grade teachers, with an average age of 41.4 years (SD = 10.8), from public and subsidized private schools. No significant differences (d = 0.09) were found in self-efficacy scores between men (M = 98.8; SD = 15.1) and women (M = 97.4; SD = 15.7), so the full sample was analyzed. The reliability coefficient was excellent (α = 0.971). The average TSES score was 97.7 (SD = 15.6), exceeding the theoretical midpoint (Mtheoretical = 72). Most teachers were in the average range of the scale (T = 40–60). These normative data enable accurate interpretation of teacher self-efficacy, facilitating targeted interventions to improve teachers’ wellbeing and professional effectiveness.